Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I was doing the following question. Using the following rules of boolean algebra:

law 1: X+X=1

law 2: X.1=X

law 3:X.Y+X.Z = X.(Y+Z)


    __  _   __ 

I have tried to simplify starting off with law 1, but I get stuck because the complements somewhat confuse me.

The bar meaning complement or 'not'

Could someone explain?

share|improve this question
This is extremely confusing since it looks like you've switched from "primes" for complements to "overbars", and you're using juxtaposition for "and" instead of &. Can you please switch it to be consistent? –  rschwieb May 8 '12 at 13:16
@rschwieb I edited, sorry for confusion. –  Xabi May 8 '12 at 13:23
The notation in the laws and the notation in the question are still completely different. If you think my solution below is answering the question you asked, I can attempt to make your post clear. –  rschwieb May 8 '12 at 13:31
Are the second and third terms $\overline{A}\overline{B}C$ or are they $\overline{AB}C$? –  robjohn Jan 17 '13 at 21:20

3 Answers 3

up vote 1 down vote accepted

If I understand correctly, the problem is to reduce $$ (\overline{A \& B} \& C) + (\overline{A} \& B \& C)+ (\overline{A \& B} \& C) +(A\& B \& C) $$

You can deduce from the laws that $X+X=X$, so this is clearly already

$$ =(\overline{A \& B} \& C) + (\overline{A} \& B \& C)+(A\& B \& C) $$ By law 3, then law 1, then law 2: $ (\overline{A} \& B \& C)+(A\& B \& C)=(\overline{A}+A)\&B\& C=1\&B\& C=B\&C $, so the original expression is now:

$$ =(\overline{A \& B} \& C)+B\&C $$

By De Morgan's laws $\overline{A \& B}=(\overline{A}+\overline{B})$, and you can deduce the rest from your laws:

$$ =(\overline{A} + \overline{B}) \& C+B \& C =(\overline{A} + \overline{B}+B) \& C $$

$$ =(\overline{A} + 1) \& C=1\&C=C $$

share|improve this answer
This is perfect Thank you! –  Xabi May 8 '12 at 13:50

=C(AB+A'B')+ A'C(B+B') =C(1) + A'C(1) =C + A'C =C(1+A') =C according to (1+x=1)

share|improve this answer

There are four variables P,B,M,O

The expression is


What would be the simplified form of the above expression using boolean laws which are : _ law 1: X+X=1

law 2: X.1=X

law 3:X.Y+X.Z = X.(Y+Z) and so on ...!

Can you please help me ,I'm not getting that simplified form...

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.